From flowers to pollinators: Dietary exposure of honey bees, bumble bees and solitary bees to trace elements across European fields - Maciej Durkalec; Agnieszka Nawrocka; Petru Jitaru; Marie-Pierre Chauzat; Marion Laurent; Matthias Albrecht; Cecilia Costa; Pilar De la Rúa; Alexandra-Maria Klein; Marika Mänd; Simon G. Potts; Maj Rundlöf; et al. (Journal of Hazardous Materials, 2026)

Exploring climate-driven phenological mismatches in pears, pests and natural enemies: a multi-model approach - Laura A. Reeves; Tim Belien; Deepa Senapathi; Michael P. D. Garratt; Michelle T. Fountain (Journal of Pest Science, 2025)
Pear psyllid ( Cacopsylla pyri ) is the dominant pest of UK pear orchards, with an estimated cost of £5 million per annum. Insecticide withdrawal and increased pesticide resistance of C. pyri have led many growers to depend more on natural enemies for pest management, including earwigs. However, there is concern how phenological events may shift with future climate change, which may result in phenological mismatches. This study aimed to determine shifts in timing of phenological events within an agroecosystem and predict phenological mismatches or synchronies between trophic levels. We evaluated three models: the C. pyri phenology model, the earwig degree day model and the PhenoFlex model (flowering time). Phenological events predicted by models included: first, full and last flowering time for Pyrus communis ; peak psyllid abundance date for first-generation (G1) C. pyri nymphs and second-generation (G2) eggs, nymphs and adults; and peak abundance date for stage 4 Forficula auricularia and adults. Findings indicated that the timing of phenological events was advancing for all trophic levels, becoming significantly earlier under the current time period. Furthermore, predictions indicated that timing events would continue to advance under the RCP8.5 scenario. However, not all phenological events advanced at the same rate; the date of peak C. pyri G1 nymph abundance advanced at a higher rate than full flowering time, which could result in a phenological mismatch by 2071. Conversely, C. pyri and F. auricularia showed phenological synchrony, with peak abundance dates advancing at a similar rate, which could be beneficial for future biological control.

Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

Anthropogenic impacts drive habitat suitability in South Asian bats - Aditya Srinivasulu; Deepa Senapathi; Manuela González-Suárez (Biodiversity and Conservation, 2024)
Despite their diversity and importance as ecological indicators and ecosystem service providers, the macroecology of bats in South Asia is poorly understood, and until recently studies on the ecological niches of these species have been rare. This study analyses the ecogeographic predictors of habitat suitability in South Asian bats by conducting ensemble ecological niche modelling using four algorithms (random forests, artificial neural networks, multivariate adaptive regression splines, and maximum entropy) to define suitability envelopes for 48 selected bat species, based on topographic, hydrographic, land-use, land-cover, and other anthropogenic impact factors. Anthropogenic impact variables showed high importance with Median Night-time Light being the biggest driver of habitat suitability for most of the study species with generally lower suitability of brighter areas. Projected suitable areas for individual species covered between 6.28% and 22.98% of the study area. Regions such as the Thar desert of northwestern India were consistently identified to have low suitability. The Western Ghats in India, the Himalayas in Bhutan, northern India, and Nepal, and Sri Lanka were identified as suitability hotspots for more than half the studied species overlapping with human-impacted habitats. This study offers insight into the impacts of anthropogenic pressure on the macroecology of bats in a megadiverse region and stresses the importance of analysing ecogeographic effects on ecological niches and habitat suitability, which can be vital to inform conservation planning and policymaking in the future.

Intraguild Predation or Spatial Separation? The efficacy and Interactions of Two Natural Enemy Species for the Biological Control of Pear Psyllid (Cacopsylla pyri) - Laura A. Reeves; Michelle T. Fountain; Michael P. D. Garratt; Deepa Senapathi (Journal of Insect Behavior, 2024)
Pear psyllid ( Cacopsylla pyri ) is a persistent pest to the pear industry; with an estimated cost of £5 million per annum in the UK alone. This phloem feeding insect is resistant to a large proportion of approved pesticides, necessitating the use of alternative control strategies. Many pear growers practice integrated pest management (IPM) of pear psyllid, focusing on maximizing natural enemy populations, whilst minimizing the use of agrochemical sprays. The anthocorid Anthocoris nemoralis and the European earwig Forficula auricularia are particularly effective at controlling pear psyllid populations during the summer months. Despite the effectiveness of both natural enemies, there is a lack of understanding on whether both species should be promoted together or separately, due to the risk of intraguild predation (IGP) or interference competition. Furthermore, abiotic factors including temperature may influence both behaviors, altering activity level and niche overlap. Although IGP and interference competition have been documented between multiple species of natural enemies neither have been studied between these two specific predators. Using microcosm experiments, olfactometer assays and survival analyses this study demonstrated whether A. nemoralis and F. auricularia can be used in synchrony to control pear psyllid. Results indicated that IGP is present; F. auricularia will consume A. nemoralis when predators are not spatially separate and in absence of psyllid prey. There was no evidence for interference competition, although both predators consumed more prey at higher temperatures. This confirms that pear growers can encourage both predators for the control of pear psyllid without losing predation efficacy.

Using a multi-scale approach to examine the effects of field margins and landscape features on predatory carabid communities in crop fields - Kelly Jowett; Alice E. Milne; Dion Garrett; Dan Blumgart; Simon G. Potts; Deepa Senapathi; Jonathan Storkey (Agriculture, Ecosystems & Environment, 2024)

Novel indices reveal that pollinator exposure to pesticides varies across biological compartments and crop surroundings - Marion LAURENT; Stéphanie BOUGEARD; Lucile CARADEC; Florence GHESTEM; Matthias ALBRECHT; Mark J.F. BROWN; Joachim DE MIRANDA; Reet KARISE; Jessica KNAPP; José SERRANO; Simon G. POTTS; Maj RUNDLÖF; et al. (Science of The Total Environment, 2024)

A whole ecosystem approach to pear psyllid (Cacopsylla pyri) management in a changing climate - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Pest Science, 2024)
Whole ecosystem-based approaches are becoming increasingly common in pest management within agricultural systems. These strategies consider all trophic levels and abiotic processes within an ecosystem, including interactions between different factors. This review outlines a whole ecosystem approach to the integrated pest management of pear psyllid ( Cacopsylla pyri Linnaeus) within pear ( Pyrus communis L.) orchards, focusing on potential disruptions as a result of climate change. Pear psyllid is estimated to cost the UK pear industry £5 million per annum and has a significant economic impact on pear production globally. Pesticide resistance is well documented in psyllids, leading to many growers to rely on biological control using natural enemies during the summer months. In addition, multiple insecticides commonly used in pear psyllid control have been withdrawn from the UK and Europe, emphasising the need for alternative control methods. There is growing concern that climate change could alter trophic interactions and phenological events within agroecosystems. For example, warmer temperatures could lead to earlier pear flowering and pest emergence, as well as faster insect development rates and altered activity levels. If climate change impacts pear psyllid differently to natural enemies, then trophic mismatches could occur, impacting pest populations. This review aims to evaluate current strategies used in C. pyri management, discuss trophic interactions within this agroecosystem and highlight potential changes in the top-down and bottom-up control of C. pyri as a result of climate change. This review provides a recommended approach to pear psyllid management, identifies evidence gaps and outlines areas of future research.

Functional and Behavioral Responses of the Natural Enemy Anthocoris nemoralis to Cacopsylla pyri, at Different Temperatures - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Insect Behavior, 2023)
Anthocoris nemoralis is the dominant predator of pear sucker ( Cacopsylla pyri ) in the UK. Anthocoris nemoralis migrates into orchards in spring or is introduced as a biocontrol agent, reaching peak population levels in July-August, contributing to effective control of summer pear sucker populations. However, due to temperature dependent development and metabolism there are concerns that C. pyri populations or feeding rates may increase due to changing climatic conditions. Thus, how A. nemoralis responds to temperature, impacts its ability as a biocontrol agent. Functional response assays, monitoring attack rate and handling time of A. nemoralis and behavioral assays, using Ethovision tracking software occurred, to assess the impact of temperature on predation. Experiments were conducted at current and future July-August mean temperatures, predicted using RCP4.5 and RCP8.5 (medium and high, representative concentration pathway) emissions scenarios, using 2018 UK Climate Projections (UKCP18). All treatments demonstrated a Type II functional response, with female anthocorids demonstrating shorter handling times and higher attack rates than males. Males showed longer prey handling times at 18 °C compared to 23 °C and more time was spent active at lower temperatures for both sexes. Females did not show significant differences in attack rate or handling time in response to temperature. Overall prey consumption was also not significantly affected by temperature for either sex. This study suggests that anthocorids are likely to remain effective natural enemies under future predicted temperatures, due to non-significant differences in prey consumption.

Climate driven shifts in the synchrony of apple (Malus x domestica Borkh.) flowering and pollinating bee flight phenology - Chris Wyver; Simon G. Potts; Rowan Edwards; Mike Edwards; Deepa Senapathi (Agricultural and Forest Meteorology, 2023)

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

The role of climate in past forest loss in an ecologically important region of South Asia - Alice E. Haughan; Nathalie Pettorelli; Simon G. Potts; Deepa Senapathi (Global Change Biology, 2022)
Tropical forests in India have declined at an alarming rate over the past century, with extensive literature focusing on the high contributions of agricultural expansions to deforestation, while the effects of climate change have largely been overlooked. Climate change effects, such as increasing temperatures, drought and flooding, have already occurred, and are projected to worsen. Climate velocity, a metric that accounts for spatial heterogeneity in climate, can help identify contiguous areas under greater climate stress and potential climate refuges in addition to traditional temporal trends. Here, we examined the relative contribution of climate changes to forest loss within an area of India, Jammu, Kashmir, and Ladakh during the period 2001–2018, at two spatial (regional and study area) and two temporal (seasonal and annual) scales. This includes, for the first time, a characterization of climate velocity in the area. Our findings show that annual forest loss increased substantially over the 17‐year period examined (2001–2018), with the majority of forest loss occurring in the Northeast region. Decreases in temporal trends of temperature and precipitation were most associated with forest losses, but there was large spatial and seasonal variation in the relationship. In every region except the Northeast, forest losses were correlated with faster velocities of at least one climate variable but overlapping areas of high velocities were rare. Our findings indicate that climate changes have played an important role in past forest loss within the study area but likely remain secondary to other factors at present. We stress concern for climates velocities recorded reaching 97 km year −1 , and highlight that understanding the different regional and seasonal relationships between climatic conditions and forest distributions will be key to effective protection of the area's remaining forests as climate change accelerates.

Combined effects of agrochemicals and ecosystem services on crop yield across Europe - Vesna Gagic; David Kleijn; András Báldi; Gergely Boros; Helene Bracht Jørgensen; Zoltán Elek; Michael P. D. Garratt; G. Arjen de Groot; Katarina Hedlund; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Emily Martin; et al. (Ecology Letters, 2017)
Simultaneously enhancing ecosystem services provided by biodiversity below and above ground is recommended to reduce dependence on chemical pesticides and mineral fertilisers in agriculture. However, consequences for crop yield have been poorly evaluated. Above ground, increased landscape complexity is assumed to enhance biological pest control, whereas below ground, soil organic carbon is a proxy for several yield‐supporting services. In a field experiment replicated in 114 fields across Europe, we found that fertilisation had the strongest positive effect on yield, but hindered simultaneous harnessing of below‐ and above‐ground ecosystem services. We furthermore show that enhancing natural enemies and pest control through increasing landscape complexity can prove disappointing in fields with low soil services or in intensively cropped regions. Thus, understanding ecological interdependences between land use, ecosystem services and yield is necessary to promote more environmentally friendly farming by identifying situations where ecosystem services are maximised and agrochemical inputs can be reduced.

Evidence for long‐term regional changes in precipitation on the East Coast Mountains in Mauritius - Deepa Senapathi; Fiona Underwood; Emily Black; Malcolm A. C. Nicoll; Ken Norris (International Journal of Climatology, 2010)
Global climate change and its impacts are being increasingly studied and precipitation trends are one of the measures of quantifying climate change especially in the tropics. This study uses daily rainfall data to determine if there are changes in the long‐term trends in rainfall variability in the East Coast Mountains of Mauritius during the last few decades, and to investigate the factors influencing the trends in the inter‐annual to inter‐decadal rainfall variability. Statistical modelling has been used to investigate the trends in total seasonal rainfall, the number of rain days and the mean amount of rain per rainy days and the local, regional and large‐scale factors that affect them on inter‐annual to inter‐decadal time scales. The strongest inter‐decadal trend was found in the number of rain days for both rainfall seasons, and the other variables were found to have weak or insignificant trends. Both local factors, such as the surrounding sea surface temperatures and large‐scale phenomena such as Indian Monsoon and the El Ni ñ o Southern Oscillation were found to influence rainfall patterns. Copyright © 2009 Royal Meteorological Society